Peran media sosial dalam mengurangi risiko banjir di kota Makassar - A. Kamaruddin, Syamsu (Research Agency for Humanity and Urban, 2025)
The increasing frequency and impact of flooding in urban areas has created an urgent need for a rapid, accurate, and participatory information and mitigation coordination system. Amidst these conditions, social media has emerged as a potential tool to accelerate the dissemination of disaster information, raise public awareness, and support real-time response coordination. This study aims to assess the level of social media utilization by the public and government in Makassar City and to assess its effectiveness in disseminating information and coordinating flood mitigation. The study used a qualitative approach with a case study method. Data were collected through in-depth interviews and observations. The results indicate that social media utilization in Makassar is relatively high, with platforms such as Facebook and Instagram serving as primary channels for disaster communication. Policymakers actively use official accounts to disseminate early warnings, mitigation guidance, aid post locations, and maps of affected areas, ensuring official information reaches the public before traditional media dissemination. Meanwhile, residents use social media to report flood locations, road and organizational conditions, logistical needs, and emergency situations, enabling a more rapid community and institutional response. The speed of information dissemination through social media has been proven to be higher than conventional media, and the level of public engagement is an indicator that mitigation and warning messages resonate and are widely disseminated.